Sport and Tourism Strategies to Develop Tourist Destinations - Valeri, Marco (New Perspectives in Tourism and Hospitality Management Series, 2023)
In confronting growing concerns around environmental, social and economic issues facing sports and tourism, this collection presents different perspectives to develop new plans for future needs and problems